2019
DOI: 10.1038/s41419-019-1539-8
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance of the spindle-assembly checkpoint promotes spindle poison-mediated cytotoxicity with distinct kinetics

Abstract: Disrupting microtubule dynamics with spindle poisons activates the spindle-assembly checkpoint (SAC) and induces mitotic cell death. However, mitotic exit can occur prematurely without proper chromosomal segregation or cytokinesis by a process termed mitotic slippage. It remains controversial whether mitotic slippage increases the cytotoxicity of spindle poisons or the converse. Altering the SAC induces either mitotic cell death or mitotic slippage. While knockout of MAD2-binding protein p31 comet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
(50 reference statements)
3
5
0
Order By: Relevance
“…Moreover, their expression does not decline to baseline levels after the first round of mitosis (20-24 h). In concordance with our cell cycle profiling data, these observations suggest that LDHC silencing may result in two cell subpopulations, whereby one subset of cells undergoes mitotic slippage and the other experiences prolonged pre-mitotic arrest with likely subsequent cell death as a result of excessive, unrepaired DNA damage (Brito & Rieder, 2006; Zeng et al , 2019). Indeed, it is well known that the balance of two opposing networks, involving cyclin B1 degradation and caspase cleavage, determine mitotic cell fate (Topham & Taylor, 2013).…”
Section: Resultssupporting
confidence: 86%
“…Moreover, their expression does not decline to baseline levels after the first round of mitosis (20-24 h). In concordance with our cell cycle profiling data, these observations suggest that LDHC silencing may result in two cell subpopulations, whereby one subset of cells undergoes mitotic slippage and the other experiences prolonged pre-mitotic arrest with likely subsequent cell death as a result of excessive, unrepaired DNA damage (Brito & Rieder, 2006; Zeng et al , 2019). Indeed, it is well known that the balance of two opposing networks, involving cyclin B1 degradation and caspase cleavage, determine mitotic cell fate (Topham & Taylor, 2013).…”
Section: Resultssupporting
confidence: 86%
“…In addition, inactivating CDK1 agents can induce long-term cytotoxicity (clonogenic assay) [116]. In the present study, we observed that MCF-7 cells treated with CAT plus DOCE and ProB2 plus DOCE caused a high increase in CDK1 inhibitor.…”
supporting
confidence: 56%
“…6c, d ). A weakened SAC via perturbation of key components has been associated with mitotic errors including misaligned chromosomes, chromosome bridges, micronuclei formation, and aneuploidy 63 66 . Consistent with RIT1 M90I suppression of the SAC, RIT1 -mutant cells showed significantly higher prevalence of chromosomal abnormalities compared to parental cells (Fig.…”
Section: Resultsmentioning
confidence: 99%